Seroprevalence of syphilis among pregnant females attending antenatal clinic at a tertiary care hospital in North India - Jahan, Noor; Chandel, Swastika Singh; Chopra, Deepak; Khan, Arshiya; Khatoon, Razia (International Journal of Research in Medical Sciences, 2020)
Background: Syphilis is a sexually transmitted disease caused by bacteria named Treponema palladium, subsp. pallidum. Nearly 1.36 million pregnant women are known to be affected by syphilis in the developing countries. When left untreated syphilis during pregnancy can result in adverse fetal outcomes such as spontaneous abortion and stillbirth. Objective of the study was to evaluate the seroprevalence of syphilis among pregnant females attending Antenatal Clinic (ANC). Methods: A hospital based cross-sectional study was done over a period of six months from January to June 2019. A total of 132 pregnant females were included in the study who attended Antenatal Clinic for routine checkup whose blood samples were sent to Microbiology Laboratory for screening for syphilis by Rapid Plasma Reagin (RPR) test. Results: Out of 132 samples of pregnant females screened for syphilis, none of the sample was found reactive for syphilis by RPR test. Maximum patients (57.6%) belonged to age group 20-25 years followed by (27.3%) of 26-30 years. 30.3% patients belonged to urban areas and 69.7% patients belonged to rural areas. Majority of patients (80.3%) belonged to first trimester, followed by (18.9%) patients to second trimester and (0.8%) patients to third trimester. 78.8% patients were from lower socio-economic class followed by 12.9% patients from middle class and 8.3% patients from upper class. Conclusions: Although zero percent syphilis prevalence was observed in this study, it is recommended that free screening for syphilis should be offered to all pregnant females visiting Antenatal Clinic.